(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
Under exceptional circumstances, international (human rights) courts issue orders on provisional measures preventing a party or parties before them from taking some actions pending the final determination of a case. The main purpose of such orders is to avoid a situation where the final disposition of a matter is pre-emptively rendered fully or partly meaningless by the conduct of a party. Article 27 of the Protocol Establishing the African Court on Human and Peoples’ Rights also envisages the possibility where ‘in cases of extreme gravity and urgency’, the Court may adopt provisional measures to ‘avoid irreparable harm to persons’. The African Court on Human and Peoples’ Rights (Court), relying on this provision, has thus far issued about 50 orders of provisional measures, all of which were against respondent states. This article interrogates the Court’s practice in this regard, with the view to fleshing out its jurisprudential inconsistencies and proposing recommendations to rectify the occasional misapplication of the procedure. Close scrutiny of the Court’s jurisprudence reveals not only glaring discrepancies in approach but also, at times, unnecessary recourse to these measures even when situations do not necessarily warrant their adoption. As evidenced by the backlash from some states, which have openly expressed their refusal to comply with the Court’s orders, the unwarranted use of provisional measures is likely to render the procedure ineffective and may also negatively affect the legitimacy of the Court in the eyes of its creators, the states. Therefore, the Court should fully and strictly adhere to the legal and factual conditions required to adopt provisional measures and always be alive to the intended purpose and nature of provisional measures. The Court particularly needs to adopt a balanced approach without being too liberal or too strict, as this would be overstepping its power or abdicating its responsibility to protect human rights.